Skeletal growth and bone mineral acquisition in type 1 diabetic children; abnormalities of the GH/IGF-1 axis. (June 2017) - Raisingani, Manish; Preneet, Brar; Kohn, Brenda; Yakar, Shoshana
Abstract: Type 1 diabetes mellitus (T1DM) is one of the most common chronic diseases diagnosed in childhood. Childhood and adolescent years are also the most important period for growth in height and acquisition of skeletal bone mineral density (BMD). The growth hormone (GH)/insulin like growth factor -1 (IGF-1) axis which regulates growth, is affected by T1DM, with studies showing increased GH and decreased IGF-1 levels in children with T1DM. There is conflicting data as to whether adolescents with TIDM are able to achieve their genetically-determined adult height. Furthermore, data support that adolescents with T1DM have decreased peak BMD, although the pathophysiology of which has not been completely defined. Various mechanisms have been proposed for the decrease in BMD including low osteocalcin levels, reflecting decreased bone formation; increased sclerostin, an inhibitor of bone anabolic pathways; and increased leptin, an adipocytokine which affects bone metabolism via central and peripheral mechanisms. Other factors implicated in the increased bone resorption in T1DM include upregulation of the osteoprotegerin/ receptor-activator of the nuclear factor-κB ligand pathway, elevated parathyroid hormone levels, and activation of other cytokines involved in chronic systemic inflammation. In this review, we summarize the clinical studies that address the alterations in the GH/IGF-I axis, linear growth velocity, and BMD in children and adolescents with T1DM; and we review the possible molecular mechanisms that may contribute to an attenuation of linear growth and to the reduction in the acquisition of peak bone mass in the child and adolescent with T1DM. Highlights: The GH/IGF-1 axis is impaired in T1DM. Growth velocity and final adult height is normal in children with well-controlled T1DM. Bone mineral density (BMD) is reduced in children and adults with T1DM. Glycemic control and duration of the disease are not always related to BMD. The systemic markers osteocalcin, RANKL, leptin, PTH, sclerostin, or VD, do not show clear relationship with BMD in T1DM.